Excellent Thermoelectric Performance Realized in Copper Sulfide Magnetic Nanocomposites Via Modified Solid States Reaction - Tian‐Yu Yang; Zi‐Yuan Wang; Xi Yan; Chong‐Yu Wang; Yi‐Xin Zhang; Zhen‐Hua Ge; Jing Feng (Advanced Science)
Abstract Solid‐state reactions, which are the basic reactions involved in the preparation, processing, and application of materials, are ubiquitous in material science and chemistry research. In the fields of metallurgy and geology, a significant number of complex chemical reactions occur during the smelting of ores. Inspired by the smelting of copper concentrate, this work applies modified metallurgical chemical reactions to the field of (thermoeletric) TE materials. By controlling the reaction temperature and composition, porous copper sulfide magnetic nanocomposites can be formed. Regulating the composition generates numerous precipitates and Cu‐rich phases, and controlling the microstructure facilitates the formation of porous structures. The second phase and porous structure effectively decreased thermal conductivity. Furthermore, the introduction of ferromagnetic Fe3O4 particles plays a role in reducing carrier concentration and forming potential barrier scattering low energy carriers, which improves the Seebeck coefficient of the samples. Ultimately, the optimum figure of merit (ZT) of ≈1.3 at 773 K for the Cu1.8S + 2 wt.% Fe3O4 bulk sample and an average ZT of 0.57 over the entire operating temperature range. The modified solid states reaction between oxides and sulfides could be employed to optimize electrical and thermal transport properties for sulfide TE material, as well as sulfide batteries, sulfide photoelectric materials, and sulfide catalytic materials.